THE EFFECTS OF ADDING FOREST HONEY ON THE QUALITY OF SWEET CORN (ZEA MAYS L) YOGURT : Doi: https://doi.org/10.47918/jhts.v3i1.334 - Sofyan Tambipi; Ni Luh Arwati; Mangga, Mastin (LP2M Universitas Bina Mandiri Gorontalo, 2021)
Research on corn has shown that corn is an important source of carbohydrates in the diet of the people in Indonesia. Sweet corn has the potential to be used as an ingredient in yogurt because of its content. Yogurt is a pasteurized milk product that is then fermented using Lactobacillus bulgaricus and Streptococcus thermophillus bacteria. The present study aims to determine the quality of sweet corn yogurt which has been added with forest honey with a concentration of 8%, 10%, and 12% through the Total Plate Number (ALT) test, pH test, and organoleptic test. The research was conducted at the Laboratory of Bina Mandiri University Gorontalo. This research was an experimental method consisting of 4 treatments, namely the treatment without the addition of forest honey (Control or P0), the addition of forest honey with concentrations of 8% (P1), 10% (P2), and 12% (P3). Research shows that the addition of forest honey with various concentrations meets the quality standards of yogurt according to the Indonesian National Standard (SNI) (01-2981-2009). For the addition of 8% honey; BAL 1.1 x 107Cfu / ml, pH 4, 10% acceptability for honey 10%; BAL 1,4 x 107Cfu / ml, pH 4 and 20% acceptability for adding 12% of honey; BAL 1.4 x 107Cfu / ml, pH 4 and 60% acceptance. It can be concluded that the study has the effect of adding forest honey on the quality of sweet corn (Zea Mays L) yogurt.